Tree Tobacco Extract (Nicotiana glauca) as a Plithogenic Bioinsecticide Alternative for Controlling Fruit Fly (Drosophila immigrans) using n-SuperHyperGraphs - Emerson Jácome Mogro; Jaime Rojas Molina; Gustavo José Sandoval Cañas; Pablo Herrera Soria (Neutrosophic Sets and Systems)
Concern regarding the negative effects of synthetic pesticides has driven the development of bioinsecticides as sustainable alternatives. Consequently, Nicotiana glauca has gained prominence for its insecticidal properties due to phytochemical compounds effective against pests such as Drosophila immi grans. This study, therefore, evaluated the efficacy of Nicotiana glauca extract as a bioinsecticide by opti mizing extraction parameters and analyzing its insecticidal action under laboratory conditions across eight combined treatments. For this purpose, multiple experimental combinations were analyzed through Plithogenic n-SuperHyperGraphs, allowing a multidimensional evaluation of the attributes and properties of each treatment. Results indicated that treatment with 96% ethanol, 48 hours of maceration, and fresh leaves maximized insecticidal metabolites and pest mortality. It is concluded that Nicotiana glauca represents a promising bioinsecticide alternative for sustainable agriculture, with optimal treatments for pest control.